BUSINESS SUSTAINABILITY MODEL OF THE MSME SECTOR IN INDONESIA: THE ROLE OF FINANCIAL LITERACY, INNOVATION CAPABILITY, AND KNOWLEDGE MANAGEMENT AS PREDICTORS - Setyawati, Amelia; Sugangga, Amelia; Rahman, Iradah; Mirando, Uditha (Sekolah Tinggi Ilmu Ekonomi Sultan Agung Pematangsiantar, 2025)
This research aims to develop a business sustainability model in Indonesia's Micro, Small and Medium Enterprises sector by examining the role of financial literacy, innovation capability and knowledge management as the main predictors. The research method uses a quantitative survey design involving 350 MSME players in various industrial sectors in Indonesia. Data was collected through a structured questionnaire, which was analysed using the Structural Equation Modelling (SEM) technique to test direct and indirect relationships between variables. The research results show that financial literacy, innovation capability, and knowledge management positively and significantly influence the sustainability of MSME businesses, both partially and simultaneously. These findings provide practical implications for MSME actors and policymakers to prioritise capacity-building programs in these three areas to build a stronger sustainability foundation. In addition, this research enriches the literature regarding strategies for strengthening MSMEs in developing countries, while also opening opportunities for further studies that integrate external factors such as government support and digital technology within the framework of business sustainability models.